Biventricular function in Friedreich's ataxia: a radionuclide angiographic study. Issue 6 (June 1988) - Palagi, B; Picozzi, R; Casazza, F; Possa, M; Magri, G; Zoccarato, O; Graziano, E; Ferrari, F; Morpurgo, M
Abstract : The systolic and diastolic function of both ventricles was assessed by radionuclide angiography in 21 patients with Friedreich's ataxia and hypertrophic cardiomyopathy. The indices of systolic function of the two ventricles and those of diastolic function of the right ventricle were generally normal. But in patients with Friedreich's ataxia the time to peak filling rate divided by the diastolic time of the left ventricle was significantly larger than normal. The increase correlated with the heart rate (r = 0.79) and this suggests an alteration in the timing of ventricle filling that is more evident at high heart rates. Movement of the left ventricle was little impaired; however, in 48% of the patients with Friedreich's ataxia the right ventricle showed evidence of hypokinetic segments. Because there is a tendency for congestive heart failure to develop in patients with Friedreich's ataxia, this hypokinesis of the right ventricle should be monitored at follow up.